2015
DOI: 10.1186/s11671-015-1047-4
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity of Ta-doped ZnO Nanoparticles

Abstract: A novel photocatalyst of Ta-doped ZnO nanoparticles was prepared by a modified Pechini-type method. The antimicrobial study of Ta-doped ZnO nanoparticles on several bacteria of Gram-positive Bacillus subtilis (B. subtilis) and Staphylococcus aureus (S. aureus) and Gram-negative Escherichia coli (E. coli) and Pseudomonas aeruginosa (P. aeruginosa) were performed using a standard microbial method. The Ta-doping concentration effect on the minimum inhibitory concentration (MIC) of various bacteria under dark ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(67 citation statements)
references
References 38 publications
4
54
3
1
Order By: Relevance
“…Guo et al 38 found particles of pure ZnO PP, also of approximately spherical shape and diameters of 10 to 60 nm, relatively smaller but close to those found in the present work.…”
supporting
confidence: 90%
“…Guo et al 38 found particles of pure ZnO PP, also of approximately spherical shape and diameters of 10 to 60 nm, relatively smaller but close to those found in the present work.…”
supporting
confidence: 90%
“…For instance, ZnO NPs doped with fluorine generate more ROS than ZnO NPs, resulting in greater damage to bacterial cells. 164,165 The O content at the surface of the ZnO NPs is the key factor regulating antimicrobial effectiveness against both Gram-negative and Gram-positive bacteria. 166 Nano-TiO 2 is widely applied in orthopedic and dental implants, which have antibacterial activity that can reduce the formation of biofilms.…”
Section: Doping Modificationmentioning
confidence: 99%
“…[5] Zinc oxide nanoparticles showed antibacterial activity against various organisms. [6,7] The doping of ZnO nanoparticles showed more antibacterial activity than the pure ZnO nanoparticles. [8] Doping of MgO to ZnO has a wider band gap of 7.3eV.…”
Section: Introductionmentioning
confidence: 99%